KINERJA KEUANGAN DAN PENYALURAN DANA SOSIAL YANG BERLANDASKAN TRI HITA KARANA (THK) PADA LEMBAGA PERKREDITAN DESA - Ni Wayan Alit Erlina Wati (UNHI Press, 2020)
Financial performance is the result of decisions based on an assessment of the company's capabilities, both in terms of liquidity, activity, solvency and profitability made by the company's management. The purpose of this study was to determine the effect of ROA, CAR, and CR on the distribution of social funds based on Tri Hita Karana. This research was conducted at the Lembaga Perkreditan Desa, Desa Adat in Penatih village. The type of data used is quantitative from 2014-2016 in the form of a quarterly balance sheet, income statement, trial balance and social fund ledger. Data collection is done through documentation and observation. The analysis technique used is multiple linear regression. The results found that Return on Assets (ROA), Capital Adequacy Ratio (CAR) and Current Ratio (CR) have a positive affect on the distribution of social funds based on Tri Hita Karana. This shows that the higher the profit generated, the better the financial performance of the LPD where most of the social funds channeled are related to parhyangan and pawongan.